Mn < 2 + >-doped metal organic gel composite material as well as preparation method and application thereof

Through the Mn2+ doped metal-organogel composite material, the Mn2+ and Ce4+/Ce3+ ions are used to participate in the redox reaction, the problems of narrow pH range, harsh reaction conditions and difficult product treatment in the antibiotic degradation of iron Fenton catalysts are solved. Efficient antibiotic degradation is achieved and costs are reduced.

CN119186645AActive Publication Date: 2024-12-27ANHUI NORMAL UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411326498.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The existing ironfenton catalysts have problems such as narrow pH range, harsh reaction conditions, difficult product treatment after catalysis, and low H2O2 utilization rate during the antibiotic degradation process, resulting in low antibiotic removal efficiency and high cost.

Method used

Using Mn2+ doped metal organic gel composite material, a three-dimensional network structure is formed by reacting aspartic acid and cerium salt in an alkaline solvent, uniformly doping manganese ions, and using Mn2+ and Ce4+/Ce3+ ions to participate in the redox reaction, realizing Fenton-like catalytic effect while avoiding the defects of traditional iron Fenton catalysts.

Benefits of technology

It improves the photocatalytic degradation efficiency of antibiotics, enhances the redox capacity of catalysts, solves the pollution problem of antibiotics in water, avoids the defects of traditional catalysts, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186645A_ABST
    Figure CN119186645A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of antibiotic degradation, and discloses a Mn < 2 + >-doped metal organic gel composite material as well as a preparation method and application thereof. The preparation method comprises the following steps: stirring asparaginic acid and cerium salt in an alkaline solvent, and standing to obtain metal organic gel; and dropwise adding a soluble manganese salt solution into the metal organic gel, standing, and drying, so that manganese ions are uniformly doped and dispersed into the metal organic gel, thereby obtaining the Mn < 2 + > doped metal organic gel composite material. The preparation method is simple and low in cost, the Mn < 2 + >-doped metal organic gel composite material has high porosity, high specific surface area and good adsorption effect on reaction substrate molecules, antibiotic molecules can be adsorbed to be close to metal ions Mn < 3 + > / Mn < 2 + > and Ce < 4 + > / Ce < 3 + > so as to participate in oxidative degradation reaction of the antibiotic molecules, and the degradation rate of the antibiotic molecules is increased. Furthermore, the antibiotic degradation capability of the photocatalytic Fenton-like reaction of the material is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of antibiotic degradation, and in particular to a Mn 2+ Doped metal organic gel composite material and preparation method and application thereof. Background Art

[0002] As humans improve their quality of life and pursue health and longevity, the problem of environmental water pollution caused by the abuse of various drugs such as antibiotics is becoming increasingly serious. These pollutants are widely present in rivers and groundwater, and they directly or indirectly affect the survival of various animals, plants and other organisms on the earth. Among various antibiotics, tetracycline hydrochloride has a broad spectrum of antibacterial properties and a large output, and is used frequently. Therefore, effectively removing tetracycline hydrochloride from wastewater has become an important task to protect the environment and safeguard human health.

[0003] In order to solve the above technical problems, the existing technologies mainly adopt adsorption method, flocculation method, biodegradation method and Fenton reaction. Among them, the Fenton reaction can be carried out under conditions close to ambient temperature and pressure, and the oxidative free radicals produced can degrade organic pollutants such as antibiotics into non-toxic substances such as CO2, H2O and inorganic salts, etc., which is one of the most effective technologies for removing wastewater pollutants. However, the iron Fenton catalyst used in the traditional Fenton reaction has the following disadvantages: (1) narrow applicable pH range; (2) acidic reaction conditions; (3) large amount of iron sludge produced after the reaction, which is difficult to handle; (4) low H2O2 utilization rate, etc.

[0004] To this end, the present invention provides a Mn 2+ Doped metal organic gel composite material and preparation method and application thereof. Summary of the invention

[0005] In order to solve the problems of high requirements for the preparation of iron-Fenton catalysts, harsh reaction conditions, and difficulty in treating the subsequent catalytic products in the above-mentioned prior art, as well as the defects of low antibiotic removal efficiency and high cost, the present invention takes into account that metal manganese and cerium have multiple valence states, such as Mn 3+ / Mn 2+ and Ce 4+ / Ce 3+ , with a multivalent state similar to iron Fe 3+ / Fe 2+ The Fenton reaction properties of the present invention, therefore, the present invention attempts to provide a catalyst based on manganese ions and cerium ions, so as to achieve a Fenton-like catalyst effect while avoiding the defects of traditional iron Fenton catalysts. Therefore, the present invention provides a Mn 2+ Doped metal organic gel composite material and preparation method and application thereof.

[0006] A Mn 2+The doped metal organic gel composite material and its preparation method and application are realized by the following technical scheme:

[0007] The first object of the present invention is to provide a Mn 2+ The method for preparing the doped metal organic gel composite material comprises the following steps:

[0008] Step 1: using aspartic acid as a ligand, placing aspartic acid and cerium salt in an alkaline solvent for stirring reaction and then standing to obtain a metal organic gel with a three-dimensional network structure.

[0009] Step 2, using a soluble manganese salt solution as a doping ion source, uniformly dropping it into the metal organic gel, standing it and then drying it, so that the manganese ions provided by the soluble manganese salt solution are uniformly doped and dispersed in the metal organic gel, to obtain Mn 2+ Doped metal-organic gel composites.

[0010] It should be noted that the present invention takes into account that the coordination polymer molecules in the metal organic gel are similar to the three-dimensional network structure of the metal organic framework MOFs material, which has the advantages of large porosity and specific surface area, strong adsorption, etc. Therefore, the present invention uses the metal organic gel as a carrier and Mn 2+ As a loading substance, the target degradation product is firstly adsorbed by the metal organic gel, and then the Mn loaded on the metal organic gel is 2+ Ce on ions and metal-organic gel network nodes 4+ ions participate in the redox reaction of TC degradation, and with the assistance of H2O2, it is beneficial to form Mn 3+ / Mn 2+ and Ce 4+ / Ce 3+ The cycle of Fenton-like double redox reactions improves the redox capacity of the resulting catalyst, thereby achieving degradation of the target degradation products.

[0011] In order to ensure that the formed metal organic gel can not only serve as Mn 2+ carrier, realizing Mn 2+The uniform distribution of the aspartic acid and the good adsorption effect on the target degradation products can be achieved. In some preferred embodiments of the present invention, aspartic acid is used as a ligand. For the convenience of description, the present invention will use the English abbreviation Asp to represent aspartic acid. The cerium salt composed of cerium ions and inorganic anions is used as a cerium source, and the cerium ions and inorganic anions provided by the cerium salt are fully mixed by stirring, so that the aspartic acid and the cerium ions and inorganic anions provided by the cerium salt are fully contacted and coordinated to form a coordination polymer. Since there are inorganic anions and solvent molecules in the reaction system, the adjacent coordination polymers can further form a metal organic gel with a three-dimensional network structure under the hydrogen bonding and intermolecular action between the solvent molecules. Among them, the ratio of cerium salt to Asp has a crucial influence on the formation of the gel. When the ratio of aspartic acid to cerium salt is insufficient or exceeds a certain ratio, the gel cannot be effectively formed. Therefore, in some preferred embodiments of the present invention, the molar ratio of aspartic acid to cerium salt is limited to 1:1.8~2.2 to ensure that the two can form a metal organic gel. In some other preferred embodiments of the present invention, the molar ratio of aspartic acid to cerium salt is more preferably 1:2.

[0012] In order to ensure that the cerium salt used in the present invention can not only provide cerium ions to coordinate with Asp, but also form a coordination polymer under the action of the inorganic anions provided by the cerium salt, in some preferred embodiments of the present invention, the cerium salt used is a soluble tetravalent cerium salt, and the present invention selects a soluble tetravalent cerium salt. In other preferred embodiments of the present invention, the soluble tetravalent cerium salt used is cerium sulfate.

[0013] In order to further promote Asp to fully contact with the cerium ions provided by the cerium salt and coordinate to form a coordination polymer, in some preferred embodiments of the present invention, the reaction system also includes an alkaline solvent, so that in an alkaline environment, the carboxyl group in the ligand Asp is dehydrogenated, which further increases the solubility of Asp, and is more conducive to the coordination of Asp with the cerium ions, and forms a coordination polymer under the action of the inorganic anions provided by the cerium salt. In order to further ensure that the formed coordination polymer can construct a metal organic gel with a three-dimensional network structure under the hydrogen bonding and intermolecular action with the solvent molecules, in other preferred embodiments of the present invention, the alkaline solvent used is an aqueous solution of a soluble inorganic base. In other preferred embodiments of the present invention, the soluble inorganic base is one or both of sodium hydroxide and potassium hydroxide. In other preferred embodiments of the present invention, the concentration of the soluble inorganic base in the alkaline solvent is 0.1mol / L~1.5mol / L.

[0014] The present invention takes into account that the amount of alkaline solvent used has an impact on the formation of a gel-like metal organic gel. If the amount of alkaline solvent is too much or too little, the metal organic gel cannot be effectively formed. Therefore, in other preferred embodiments of the present invention, the molar ratio of the soluble inorganic base to the cerium salt in the alkaline solvent is 0.9 to 1.1:1.

[0015] In order to ensure that the cerium salt and Asp can be fully mixed and reacted in the alkaline solvent to form the metal organic gel by stirring, in other preferred embodiments of the present invention, the stirring time of the stirring reaction is 5 min to 10 min.

[0016] In order to further ensure that the cerium salt and Asp can be fully mixed and reacted to form the metal organic gel, in other preferred embodiments of the present invention, after the stirring is completed, the mixture is allowed to stand at room temperature for 5 minutes to 15 minutes to form the metal organic gel.

[0017] The present invention takes into account that the oxidation state of Mn contains multiple valence states. In some preferred embodiments of the present invention, the concentration of manganese ions in the soluble manganese salt solution is 0.05 mol / L to 0.15 mol / L to form Ce in the material. 4+ / Ce 3+ and Mn 3+ / Mn 2+ A double cycle of Fenton-like redox reactions is used to enhance the ability of catalytic degradation of antibiotics.

[0018] In order to ensure that the manganese ions in the added soluble manganese salt solution can be uniformly doped in the metal organic gel, in some preferred embodiments of the present invention, the standing temperature after the soluble manganese salt solution is added is room temperature, and the standing time is 5min to 15min. Due to the semi-solid nature of the gel, Mn 2+ It slowly penetrates into the gel during the standing process, and thus can be fully doped by standing.

[0019] In order to further ensure that the soluble manganese salt solution can be evenly dispersed in the metal organic gel, the Mn 2+ In some preferred embodiments of the present invention, the molar ratio of manganese ions in the soluble manganese salt solution to cerium ions in the metal organic gel is 1-2:1-6.

[0020] In order to increase the obtained Mn 2+The catalytic performance of the doped gel composite material, the present invention also dries the doped product after standing, so as to achieve the purpose of improving the adsorption of the gel by drying. And the present invention takes into account the factors of solvent water molecules contained in the gel structure. In some preferred embodiments of the present invention, the drying temperature is controlled at 45°C to 55°C to achieve gel dehydration and improve the gel porosity. The present invention takes into account that if the drying time is too short, it will not be possible to achieve the effect of improving the adsorption of the gel to adsorb the catalytic substrate antibiotic molecules; and if the drying time is too long, the solvent water is lost too much, and the gel fibers are more densely stacked, resulting in a decrease in the Fenton photocatalytic degradation effect of the material. Therefore, in some other preferred embodiments of the present invention, the drying time is controlled at 48h to 72h.

[0021] The second object of the present invention is to provide a Mn prepared by the above preparation method. 2+ Doped metal-organic gel composites.

[0022] The third object of the present invention is to provide a Mn 2+ Application of doped metal-organic gel composites in photocatalytic Fenton-like degradation of tetracycline hydrochloride.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention uses aspartic acid as a ligand and a cerium salt composed of cerium ions and inorganic anions as a cerium source, and stirs to fully mix them, so that the aspartic acid and the cerium ions and inorganic anions provided by the cerium salt are fully contacted and coordinated to form a coordination polymer. In addition, since there are inorganic anions and solvent molecules in the reaction system, adjacent coordination polymers can further form a metal organic gel with a three-dimensional network structure under the hydrogen bonding effect and intermolecular effect between the solvent molecules. And by adding Mn 2+ Dropped into the metal organic gel, Mn 2+ The doped metal organic gel composite material has simple preparation steps and low cost.

[0025] The Mn prepared by the present invention 2+ In the doped metal-organic gel composite material, the three-dimensional network structure of the metal-organic gel has the advantages of high porosity and large specific surface area. Therefore, it has a good adsorption effect on the reaction substrate molecules and can adsorb the antibiotic TC molecules near the reaction site, close to the metal ion Mn 3+ / Mn 2+ and Ce 4+ / Ce 3+ , which is convenient for participating in redox reactions, thereby enhancing the photocatalytic Fenton-like reaction degradation ability of the material, making the Mn 2+Doped metal-organic gel composites can be used to solve the water pollution problem caused by antibiotics.

[0026] The experiment of the present invention shows that the Mn 2+ With the assistance of H2O2, the doped metal-organic gel composite material can efficiently achieve photocatalytic degradation and remove tetracycline hydrochloride in aqueous solution, avoiding the defects of traditional iron-Fenton catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Mn in the present invention 2+ Schematic diagram of the preparation process of doped metal-organic gel composites.

[0028] Figure 2 This is the SEM image of Ce-Asp-Mn of Example 1.

[0029] Figure 3 1 and 2 are XRD diagrams of Ce-Asp-Mn of Example 1 and Ce-Asp of Comparative Example 1.

[0030] Figure 4 1 and 2 are BET diagrams of Ce-Asp-Mn of Example 1 and Ce-Asp of Comparative Example 1.

[0031] Figure 5 The pore size distribution diagram of Ce-Asp-Mn of Example 1 and Ce-Asp of Comparative Example 1.

[0032] Figure 6 UV DRS graphs of Ce-Asp-Mn of Example 1 and Ce-Asp of Comparative Example 1.

[0033] Figure 7 The Kubelka-Munk diagram of Ce-Asp-Mn of Example 1 and Ce-Asp of Comparative Example 1.

[0034] Figure 8 Electrochemical impedance diagrams of Ce-Asp-Mn of Example 1 and Ce-Asp of Comparative Example 1.

[0035] Fig. 9 Graphs showing the photocurrent responses of Ce-Asp-Mn of Example 1 and Ce-Asp of Comparative Example 1.

[0036] Fig.10 These are the test results of the effect of catalyst type on the performance of Fenton-like photocatalytic degradation of tetracycline hydrochloride.

[0037] Fig.11 These are the test results of the effect of the amount of manganese ion doping on the performance of Fenton-like photocatalytic degradation of tetracycline hydrochloride.

[0038] Fig.12 These are the test results of the effect of catalyst dosage on the performance of Fenton-like photocatalytic degradation of tetracycline hydrochloride.

[0039] Fig.13 These are the test results of the effect of pH value on the performance of Fenton-like photocatalytic degradation of tetracycline hydrochloride.

[0040] Fig.14 These are the test results of the effect of the initial H2O2 concentration on the performance of Fenton-like photocatalytic degradation of tetracycline hydrochloride. DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. It should be noted that in the following embodiments of the present invention, the aspartic acid used was purchased from Sinopharm Chemical Reagent Co., Ltd., and the double distilled water used was prepared by the SZ-93 double pure water distiller of Shanghai Yarong Biochemical Instrument Factory. It should also be noted that mM in the following embodiments of the present invention means mmol·L -1 ; and PBS buffer solution represents a phosphate buffersaline solution with a pH of 2 to 12.

[0042] Example 1

[0043] See also Figure 1 This embodiment provides a Mn 2+ The doped metal organic gel composite material, and the preparation method thereof is as follows:

[0044] Step 1, preparation of metal organic gel:

[0045] 1) Mix sodium hydroxide and deionized water to obtain a concentration of 1.0 mol·L -1 of sodium hydroxide solution as the alkaline solvent.

[0046] 2) Mix aspartic acid and deionized water to obtain a concentration of 0.5 mol·L -1 of aspartic acid solution.

[0047] 3) Mix Ce(SO4)2 and deionized water to obtain a concentration of 1.0 mol·L -1 of Ce(SO4)2 solution.

[0048] 4) Take 1.0 mL of the alkaline solvent prepared above, 1.0 mL of the aspartic acid solution prepared above and 1.0 mL of the Ce(SO4)2 solution prepared above, mix them, stir for 10 minutes, mix well, and then let it stand for 5 minutes to obtain a light yellow opaque gel, i.e., the metal organic gel.

[0049] Step 2, doping with Mn 2+ :

[0050] Take 10 μL of the solution with a concentration of 0.1 mol·L -1 The MnCl2 solution was evenly dripped into the gel and waited for the Mn 2+ It was doped into the metal organic gel obtained in step 1 by a slow infiltration method, and then allowed to stand at room temperature for 10 min, and then dried at 50 ° C for 48 h to obtain Mn 2+ The doped metal organic gel composite material is denoted as Ce-Asp-Mn.

[0051] Example 2

[0052] This embodiment provides a Mn 2+ The doped metal organic gel composite material, and the preparation method thereof is as follows:

[0053] Step 1, preparation of metal organic gel:

[0054] 1) Mix sodium hydroxide and deionized water to obtain a concentration of 1.0 mol·L -1 of sodium hydroxide solution as the alkaline solvent.

[0055] 2) Mix aspartic acid and deionized water to obtain a concentration of 0.5 mol·L -1 of aspartic acid solution.

[0056] 3) Mix Ce(SO4)2 and deionized water to obtain a concentration of 1.0 mol·L -1 of Ce(SO4)2 solution.

[0057] 4) Take 1.0 mL of the alkaline solvent prepared above, 1.0 mL of the aspartic acid solution prepared above and 1.0 mL of the Ce(SO4)2 solution prepared above, mix them, stir for 10 minutes, mix well, and then let it stand for 5 minutes to obtain a light yellow opaque gel, i.e., the metal organic gel.

[0058] Step 2, doping with Mn 2+ :

[0059] Take 5 μL of the solution with a concentration of 0.1 mol·L -1 The MnCl2 solution was evenly dripped into the gel and waited for the Mn 2+ It was doped into the metal organic gel obtained in step 1 by a slow infiltration method, and then allowed to stand at room temperature for 10 min, and then dried at 50 ° C for 48 h to obtain Mn 2+ The doped metal organic gel composite material is denoted as Ce-Asp-Mn.

[0060] The difference between this embodiment and embodiment 1 is only that:

[0061] In this embodiment, the concentration is 0.1 mol·L -1 The amount of MnCl2 solution used is 5 μL, that is, the molar ratio of Ce to Mn in this embodiment is 2:1.

[0062] Example 3

[0063] This embodiment provides a Mn 2+ The doped metal organic gel composite material, and the preparation method thereof is as follows:

[0064] Step 1, preparation of metal organic gel:

[0065] 1) Mix sodium hydroxide and deionized water to obtain a concentration of 1.0 mol·L -1 of sodium hydroxide solution as the alkaline solvent.

[0066] 2) Mix aspartic acid and deionized water to obtain a concentration of 0.5 mol·L -1 of aspartic acid solution.

[0067] 3) Mix Ce(SO4)2 and deionized water to obtain a concentration of 1.0 mol·L -1 of Ce(SO4)2 solution.

[0068] 4) Take 1.0 mL of the alkaline solvent prepared above, 1.0 mL of the aspartic acid solution prepared above and 1.0 mL of the Ce(SO4)2 solution prepared above, mix them, stir for 10 minutes, mix well, and then let it stand for 5 minutes to obtain a light yellow opaque gel, i.e., the metal organic gel.

[0069] Step 2, doping with Mn 2+ :

[0070] Take 40 μL of 0.1 mol·L -1 The MnCl2 solution was evenly dripped into the gel and waited for the Mn 2+ It was doped into the metal organic gel obtained in step 1 by a slow infiltration method, and then allowed to stand at room temperature for 10 min, and then dried at 50 ° C for 48 h to obtain Mn 2+ The doped metal organic gel composite material is denoted as Ce-Asp-Mn.

[0071] The difference between this embodiment and embodiment 1 is only that:

[0072] In this embodiment, the concentration is 0.1 mol·L -1 The amount of MnCl2 solution used is 40 μL, that is, the molar ratio of Ce to Mn in this embodiment is 1:4.

[0073] Example 4

[0074] This embodiment provides a Mn 2+ The doped metal organic gel composite material, and the preparation method thereof is as follows:

[0075] Step 1, preparation of metal organic gel:

[0076] 1) Mix sodium hydroxide and deionized water to obtain a concentration of 1.0 mol·L -1 of sodium hydroxide solution as the alkaline solvent.

[0077] 2) Mix aspartic acid and deionized water to obtain a concentration of 0.5 mol·L -1 of aspartic acid solution.

[0078] 3) Mix Ce(SO4)2 and deionized water to obtain a concentration of 1.0 mol·L -1 of Ce(SO4)2 solution.

[0079] 4) Take 1.0 mL of the alkaline solvent prepared above, 1.0 mL of the aspartic acid solution prepared above and 1.0 mL of the Ce(SO4)2 solution prepared above, mix them, stir for 10 minutes, mix well, and then let it stand for 5 minutes to obtain a light yellow opaque gel, i.e., the metal organic gel.

[0080] Step 2, doping with Mn 2+ :

[0081] Take 60 μL of 0.1 mol·L -1 The MnCl2 solution was evenly dripped into the gel and waited for the Mn 2+ It was doped into the metal organic gel obtained in step 1 by a slow infiltration method, and then allowed to stand at room temperature for 10 min, and then dried at 50 ° C for 48 h to obtain Mn 2+ The doped metal organic gel composite material is denoted as Ce-Asp-Mn.

[0082] The difference between this embodiment and embodiment 1 is only that:

[0083] In this embodiment, the concentration is 0.1 mol·L -1 The amount of MnCl2 solution used is 60 μL, that is, the molar ratio of Ce to Mn in this embodiment is 1:6.

[0084] Comparative Example 1

[0085] This comparative example provides a metal organic gel material, and its preparation method is as follows:

[0086] 1) Mix sodium hydroxide and deionized water to obtain a concentration of 1.0 mol·L -1 of sodium hydroxide solution as the alkaline solvent.

[0087] 2) Mix aspartic acid and deionized water to obtain a concentration of 0.5 mol·L -1 of aspartic acid solution.

[0088] 3) Mix Ce(SO4)2 and deionized water to obtain a concentration of 1.0 mol·L -1 of Ce(SO4)2 solution.

[0089] 4) Take 1.0 mL of the alkaline solvent prepared above, 1.0 mL of the aspartic acid solution prepared above and 1.0 mL of the Ce(SO4)2 solution prepared above, mix them, stir for 10 minutes, mix well, and then let it stand for 5 minutes to obtain a light yellow opaque gel, that is, a metal organic gel, namely Ce-Asp.

[0090] That is, the difference between this comparative example and Example 1 is only that:

[0091] This comparative example does not carry out Mn 2+ Doping.

[0092] Experimental Section

[0093] (I) Scanning electron microscope test

[0094] The present invention takes the Ce-Asp-Mn of Example 1 as an example and performs an electron scanning electron microscope test on it, and the test results are Figure 2 shown.

[0095] Depend on Figure 2 It can be seen that the morphology of the Ce-Asp-Mn xerogel in Example 1 is aggregated spherical objects with holes. This indicates that the addition of Mn 2+ Part of Ce in postmetallic organic polymer Ce-Asp 4+ Mn 2+ Restore to Ce 3+ , and SO4 added as raw material 2- They combine to form Ce2(SO4)3 nanoparticles, resulting in partial destruction of the gel network and the dispersion of the nanoparticles on the gel network.

[0096] (ii) XRD test

[0097] The present invention takes Ce-Asp-Mn of Example 1 and Ce-Asp of Comparative Example 1 as examples, and performs XRD tests on them respectively, and the test results are Figure 3 shown.

[0098] Depend on Figure 3 It can be seen that the Ce-Asp-Mn gel composite material of Example 1 contains a certain amount of Ce2(SO4)3. This indicates that Mn 2+ Doped in the Ce-Asp gel network, some Ce4+ Mn 2+ Restore to Ce 3+ , with SO4 2- Combined into Ce2(SO4)3 nanoparticles.

[0099] (III) BET adsorption test

[0100] The present invention takes Ce-Asp-Mn of Example 1 and Ce-Asp of Comparative Example 1 as examples, and performs BET adsorption tests on them respectively. The test method is as follows: using a JW-DX400 specific surface area analyzer, taking 100 mg of sample, vacuum drying and activating at 120°C for about 5 hours, placing the sample on the instrument, and measuring the adsorption isotherm at a temperature of 77.35K under liquid N2. According to the adsorption isotherm data, the BET equation is used for fitting to obtain the slope and intercept of the adsorption isotherm. According to the BET equation, the specific surface area is calculated. And the test results Figure 4 shown.

[0101] Depend on Figure 4 It can be seen that the Ce-Asp of Comparative Example 1 and the Ce-Asp-Mn of Example 1 both present a typical type IV curve accompanied by a hysteresis loop, indicating that they are both mesoporous materials. The BET specific surface area of ​​the Ce-Asp gel of Comparative Example 1 is 5.3289 m 2 / g, while the specific surface area of ​​Ce-Asp-Mn in Example 1 is 18.3359m 2 / g, this surface Mn 2+ After doping, the adsorption capacity of Ce-Asp gel can be significantly enhanced.

[0102] (IV) Pore size distribution test

[0103] The present invention takes Ce-Asp-Mn of Example 1 and Ce-Asp of Comparative Example 1 as examples, and performs BET tests on them respectively. The pore size distribution is calculated by BET data, and the pore size distribution is as follows: Figure 5 shown.

[0104] Depend on Figure 5 It can be seen that the pore size distribution of Ce-Asp in Comparative Example 1 is significantly larger than that of Ce-Asp-Mn in Example 1. According to the BET data calculation results, the average pore radius of Ce-Asp-Mn in Example 1 is about 2 nm, which may be caused by the agglomeration of the Ce-Asp-Mn composite material.

[0105] (V) UV-visible diffuse reflectance spectrum test

[0106] The present invention takes Ce-Asp-Mn of Example 1 and Ce-Asp of Comparative Example 1 as examples, and performs UV-visible diffuse reflectance spectrum tests on them respectively.

[0107] The test conditions are: using UV-2600i ultraviolet spectrophotometer. Take 10 mg of solid sample and place it on the MgCl2 white plate, measure the absorbance, and obtain the DRS spectrum. And the test results Figure 6 shown.

[0108] Depend on Figure 6 It can be seen that Ce-Asp of Comparative Example 1 and Ce-Asp-Mn of Example 1 have obvious solar light absorption rate near 420nm. This shows that both Ce-Asp and Ce-Asp-Mn materials can absorb solar energy and have photocatalytic properties.

[0109] (VI) Band gap energy calculation

[0110] The present invention takes the Ce-Asp-Mn of Example 1 and the Ce-Asp of Comparative Example 1 as examples, and uses the UV-visible diffuse reflectance DRS data to make a Kubelka-Munk curve. 2 The relationship between the band gap energy and the photon energy (hv) was calculated. Figure 7 shown.

[0111] Figure 7 is the Kubelka-Munk diagram of Ce-Asp-Mn of Example 1 and Ce-Asp of Comparative Example 1, and is represented by Figure 7 It can be seen that the E of Comparative Example 1 g is 2.13 eV, and the E of Ce-Asp-Mn in Example 1 is g is 2.51eV. This indicates that the Ce-Asp gel is doped with Mn 2+ After that, the band gap energy increases and the photocatalytic activity improves.

[0112] (VII) Electrochemical impedance test

[0113] The present invention takes Ce-Asp-Mn of Example 1 and Ce-Asp of Comparative Example 1 as examples, and performs electrochemical impedance tests on them respectively.

[0114] The test conditions are: electrochemical test was performed using a CHI760E electrochemical analyzer, and the electrolyte solution was 1.0 mol·L -1 Weigh 10 mg of the catalyst, disperse it in 80 μL of anhydrous ethanol solution, add 4 drops of 5% naphthol, disperse it by ultrasonic, and then evenly apply it to 1.0 cm 2 The working electrode was made on the ITO conductive glass. The scanning rate was 0.1V / sec, the test potential was 2V, and the scanning window was kept at +2V~-2V (vsAg / AgCl). The sensitivity was 1.0×10 -6 A / V, running time 400s.

[0115] And the test results Figure 8 shown.

[0116] Figure 8 is the electrochemical impedance diagram of Ce-Asp-Mn of Example 1 and Ce-Asp of Comparative Example 1, and Figure 8 It can be seen that the impedance curve diameter of the Ce-Asp-Mn composite material of Example 1 is smaller and the charge transfer resistance is smaller than that of the Ce-Asp of Comparative Example 1. This indicates that the charge transfer ability of the Ce-Asp-Mn prepared by the method of the present invention is stronger.

[0117] (VIII) Photocurrent response test

[0118] The present invention takes Ce-Asp-Mn of Example 1 and Ce-Asp of Comparative Example 1 as examples, and conducts photocurrent response tests on them respectively. The test method is as follows: the instrument and test conditions are the same as those of the electrochemical impedance test, except that a xenon lamp is required to irradiate the sample during the photoelectric response test. And the test results Fig. 9 shown.

[0119] Fig. 9 is the photocurrent response diagram of Ce-Asp-Mn of Example 1 and Ce-Asp of Comparative Example 1, and Fig. 9 It can be seen that when the light is turned off and on, the photocurrent generated by Ce-Asp-Mn under visible light irradiation is significantly enhanced compared with Ce-Asp gel. This indicates that the transfer speed of photoinduced carriers in Ce-Asp-Mn is faster, confirming that the incorporation of Mn into the gel 2+ , inhibiting the recombination rate of photogenerated electron-hole pairs, thereby improving the photocurrent performance of the material and enhancing its photocatalytic ability.

[0120] (IX) Performance test of Fenton-type photocatalytic degradation of tetracycline hydrochloride

[0121] 1) Effect of catalyst type on the performance of Fenton-like photocatalytic degradation of tetracycline hydrochloride

[0122] The present invention uses Ce-Asp-Mn of Example 1 and Ce-Asp of Comparative Example 1 as catalysts, and tests the degradation effects of Ce-Asp-Mn and Ce-Asp on photocatalytic degradation of tetracycline hydrochloride in a H2O2 environment, respectively, and the test group of Example 1 is recorded as Ce-Asp-Mn+H2O2, and the test group of Comparative Example 1 is recorded as Ce-Asp+H2O2; the experimental group without adding catalyst and H2O2 is used as a blank control, recorded as TC+H2O2; the experimental group without adding any catalyst is used as control group 1, recorded as TC; the experimental group only adding Ce-Asp-Mn of Example 1 is used as control group 2, recorded as Ce-Asp-Mn; all are tested using the same test method, and the test results are as follows: Fig.10 shown.

[0123] The test method is:

[0124] The photocatalytic degradation reaction was carried out at room temperature. PBS buffer solution was used and the pH of the reaction solution was adjusted from 0.1 mol·L -1 HCl solution or 0.1 mol·L -1 Adjust with NaOH solution.

[0125] Take 100 mg of the above catalyst and add it to 100 mL of TC solution. Stir it in the dark for 30 minutes under 500W xenon lamp to reach adsorption / desorption equilibrium. Take 3 mL of the mixed solution and centrifuge it to obtain a clear solution. Measure the TC residual concentration on a UV spectrophotometer at the maximum absorption peak of 371 nm.

[0126] The photocatalytic efficiency e is calculated according to formula 1:

[0127]

[0128] In Formula 1, C0 and C represent the concentration of TC before and after photoexcitation, respectively.

[0129] Fig.10 The test results show the effect of catalyst type on the performance of Fenton-like photocatalytic degradation of tetracycline hydrochloride, and the Fig.10 It can be seen that: in the absence of a catalyst, the photodegradation reaction of TC can be ignored, indicating that TC is very stable and not easy to decompose. In the adsorption / desorption equilibrium experiment, the adsorption rates of TC on Ce-Asp and Ce-Asp-Mn were about 40% and 50%, respectively. The adsorption capacity of Ce-Asp-Mn is slightly higher than that of Ce-Asp. In the presence of H2O2 and the action of the Fenton-like catalyst Ce-Asp-Mn, the photodegradation efficiency of TC is significantly improved, and is as high as 98%. This shows that Mn 2+ Doping into Ce-Asp gel improves the Fenton-like photocatalytic degradation ability of TC.

[0130] 2) Effect of manganese ion doping amount on the performance of Fenton-like photocatalytic degradation of tetracycline hydrochloride

[0131] The present invention uses Examples 1 to 4 as photocatalysts, and tests the photocatalytic degradation of tetracycline hydrochloride with the assistance of H2O2 on the catalysts prepared with different amounts of manganese ions. The test results show that Fig.11 shown. Fig.11 , Ce:Mn=1:1 represents Example 3, Ce:Mn=2:1 represents Example 2, Ce:Mn=1:4 represents Example 3, and Ce:Mn=1:6 represents Example 4.

[0132] The test method is: use a 500W Xe lamp to simulate sunlight. At room temperature, add 20mg of photocatalyst and 20mg of tetracycline hydrochloride into 50mL of aqueous solution containing PBS buffer solution, and disperse by ultrasound. -1 The hydrochloric acid solution and the concentration are 1 mol·L -1 The solution pH was adjusted to 7 by adding sodium hydroxide solution. Before photocatalysis, the suspension was stirred for 30 min in the dark to allow the substrate and catalyst to reach adsorption / desorption equilibrium. Then, 20 mmol·L -1 10 mL of 30% H2O2 solution was added, and then transferred to a Xe lamp light source for irradiation and timing was started. 3 mL of the suspension was taken out every 5 minutes, the supernatant was collected by centrifugation, and the absorption at 371 nm was measured with a liquid UV spectrophotometer to calculate the TC degradation rate.

[0133] Fig.11 The test results show that the amount of manganese ion doping affects the performance of Fenton-like photocatalytic degradation of tetracycline hydrochloride. Fig.11 It can be seen that when the doping amount of manganese ions is too much or too little, the photocatalytic degradation effect of tetracycline hydrochloride cannot be effectively improved. Therefore, the effective Ce / Mn ratio of the present invention is 1:1-4, and the catalytic effect is best.

[0134] 3) Test results of the effect of catalyst dosage on the performance of Fenton-like photocatalytic degradation of tetracycline hydrochloride

[0135] The present invention adopts the following test methods to test the degradation effect of the catalyst on the photocatalytic degradation of tetracycline hydrochloride in a H2O2 environment, and the test results are Fig.12 shown.

[0136] The test method is as follows: a 500W Xe lamp is used to simulate sunlight. At room temperature, 30mg of Ce-Asp-Mn prepared in Example 1 is taken as a photocatalyst, and it is added to 50mL of an aqueous solution containing a PBS buffer solution with 20mg of tetracycline hydrochloride, and ultrasonically dispersed. 0.1mol·L-1 HCl solution and 0.1 mol·L -1 The solution pH was adjusted to 7 by adding NaOH solution. Before photocatalysis, the suspension was stirred for 30 min in the dark to allow the substrate and catalyst to reach adsorption / desorption equilibrium. Then, 20 mmol·L -1 10 mL of 30% H2O2 solution was added, and then transferred to a Xe lamp light source for irradiation and timing was started. 3 mL of the suspension was taken out every 5 minutes, the supernatant was collected by centrifugation, and the absorption at 371 nm was measured with a liquid UV spectrophotometer to calculate the TC degradation rate.

[0137] Fig.12 The test results are as follows: Fig.12 It can be seen that the optimal catalyst dosage is 30 mg.

[0138] 4) Test results of the effect of pH value on the performance of Fenton-like photocatalytic degradation of tetracycline hydrochloride

[0139] The present invention adopts the following test method to test the photocatalytic degradation effect of tetracycline hydrochloride under different pH values ​​and H2O2 assisted reaction, and the test results are Fig.13 shown.

[0140] The test method is as follows: a 500W Xe lamp is used to simulate sunlight. At room temperature, 30mg of Ce-Asp-Mn prepared in Example 1 is taken as a photocatalyst, and it and 20mg of tetracycline hydrochloride are added to 50mL of an aqueous solution containing PBS buffer solution, and ultrasonically dispersed. Then, 0.1mol·L -1 HCl solution or 0.1 mol·L -1 The pH of the solution was adjusted to 3.7, 4.1, 5.4, 6.2, 7.6 and 9.3 by adding 20 mmol·L NaOH solution. Before photocatalysis, the suspension was stirred for 30 min in the dark to achieve adsorption / desorption equilibrium between the substrate and the catalyst. -1 10 mL of 30% H2O2 solution was added, and then transferred to a Xe lamp light source for irradiation and started timing. 3 mL of the suspension was taken out every 5 minutes, the supernatant was collected by centrifugation, and the absorption at 371 nm was measured with a liquid UV spectrophotometer to calculate the degradation rate.

[0141] Fig.13 The results are the test results of the effect of solution pH on the performance of Fenton-like photocatalytic degradation of tetracycline hydrochloride, and Fig.13 It can be seen that the catalyst degradation performance is best when the solution pH value is 6.2.

[0142] 5) Test results of the effect of initial H2O2 concentration on the performance of Fenton-like photocatalytic degradation of tetracycline hydrochloride

[0143] The present invention adopts the following test method to test the degradation effect of the catalyst in the H2O2 environment and the initial concentration of H2O2 on the photocatalytic degradation of tetracycline hydrochloride, and the test results are Fig.14 shown.

[0144] The test method is as follows: a 500W Xe lamp is used to simulate sunlight. At room temperature, 20 mg of Ce-Asp-Mn prepared in Example 1 is taken as a photocatalyst, and it is added to 50 mL of an aqueous solution containing a PBS buffer solution with 20 mg of tetracycline hydrochloride, and ultrasonically dispersed. Then, 0.1 mol·L -1 HCl solution and 0.1 mol·L -1 The pH of the solution was adjusted to 7 with NaOH solution. Before photocatalysis, the suspension was stirred for 30 min in the dark to allow the substrate and catalyst to reach adsorption / desorption equilibrium. After that, 10 mL of H2O2 solution with concentrations of 9.8 mM, 14.7 mM, 19.6 mM and 24.5 mM were added, respectively, and then transferred to the Xe light source for irradiation and timing was started. 3 mL of the suspension was taken out every 5 min, the supernatant was collected by centrifugation, and the absorption at 371 nm was measured with a liquid UV spectrophotometer to calculate the TC degradation rate.

[0145] Fig.14 The results are the effects of the initial concentration of H2O2 on the performance of Fenton-like photocatalytic degradation of tetracycline hydrochloride, and the Fig.14 It can be seen that the catalytic performance is best when the initial concentration of H2O2 is 19.6 mM.

[0146] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A Mn 2+ The method for preparing a doped metal organic gel composite material is characterized in that: The following steps are involved: Aspartic acid is used as a ligand, and a cerium salt composed of cerium ions and inorganic anions is used as a cerium source. The aspartic acid and the cerium salt are placed in an alkaline solvent for stirring reaction, and then allowed to stand to coordinate the aspartic acid with the cerium ions provided by the cerium salt, and a coordination polymer is formed under the action of the inorganic anions provided by the cerium salt; adjacent coordination polymers are constructed to form a metal organic gel with a three-dimensional network structure through hydrogen bonding and intermolecular interactions with solvent molecules; A soluble manganese salt solution is used as a doping ion source, and the solution is uniformly added to the metal organic gel, and then dried after standing, so that the manganese ions provided by the soluble manganese salt solution are uniformly doped and dispersed in the metal organic gel to obtain Mn 2+ Doped metal-organic gel composites; The alkaline solvent is an aqueous solution of a soluble inorganic base.

2. The preparation method according to claim 1, characterized in that The cerium salt is a soluble tetravalent cerium salt.

3. The preparation method according to claim 1, characterized in that: The molar ratio of the soluble inorganic base to the cerium salt in the alkaline solvent is 0.9-1.1:

1.

4. The preparation method according to claim 1, characterized in that: The concentration of the soluble inorganic base in the alkaline solvent is 0.1 mol / L to 1.5 mol / L.

5. The preparation method according to claim 1, characterized in that: The molar ratio of the aspartic acid to the cerium salt is 1:1.8-2.

2.

6. The preparation method according to claim 1, characterized in that: The concentration of manganese ions in the soluble manganese salt solution is 0.05 mol / L to 0.15 mol / L; the molar ratio of manganese ions in the soluble manganese salt solution to cerium ions in the metal organic gel is 1 to 2:1 to 6.

7. The preparation method according to claim 1, characterized in that: The stirring time of the stirring reaction is 5 min to 15 min.

8. The preparation method according to claim 1, characterized in that: The standing temperature after the dropwise addition of the soluble manganese salt solution is room temperature, and the standing time is 5 to 15 minutes.

9. Mn prepared by the preparation method according to any one of claims 1 to 8 2+ Doped metal-organic gel composites.

10. The Mn according to claim 9 2+ Application of doped metal-organic gel composites in photocatalytic Fenton-like degradation of antibiotics.

Citation Information

Patent Citations

  • Method for preparing doped-modified TiO2 / graphene composite material

    CN103861575A

  • Preparation and application of novel nano-heterostructure solar photocatalyst

    CN104785304A

  • Preparation method for sol-gel one-step low-temperature synthesis of pure-phase Bi25F3O40 / ZnO photocatalyst

    CN106040251A

  • Preparation method of cerium-manganese metal ion modified aluminate photocatalyst

    CN111151242A

  • Conductive metal organic gel NiMn MOG and synthesis method and application thereof

    CN113035575A